Gambaran Karakteristik Pasien Kanker yang Menjalani Kemoterapo dan Radiasi di Ruang Kemoterapi Sanjiwani RSUP Sanglah Denpasar - Dewi, Ayudia Rasita; Nurhesti, Putu Oka Yuli; Devi, Ni Luh Putu Shinta (Coping: Community of Publishing in Nursing; Vol 8 No 3 (2020): Oktober 2020DO - 10.24843/coping.2020.v08.i03.p15, 2020)
Combination of chemotherapy and radiation is one of the options to managing cancer that expected to achieve the goal of therapy more optimally. This study aimed to describe the characteristic of cancer patients undergoing chemotherapy and radiation in Sanjiwani Chemotherapy Room of Central General Sanglah Hospital, Denpasar. This was a retrospective study with purposive sampling method which determined 53 patients as sample. Conclusion of this study shows the majority of the respondents were in early elderly age (46-55 years old) were 18 people (34%), female were 40 people (75,5%). Breast cancer was the common type of cancer in female (28 people), whereas nasopharynx cancer was the common type of cancer in male patients (11 people). Average of the respondents had undergone 5 chemotherapy series and 28 radiation series. Majority of the respondents had undergone ?5 chemotherapy series and ?34 radiation series. The majority of breast, nasopharynx, cervical, and lung cancer patients consecutively had undergone chemotherapy for 4 series, 4-5 series, 4-5 series, and 5-6 series. The majority of breast, nasopharynx, cervical, and lung cancer patients consecutively had undergone radiation for 28 series, 32 nd , 35 th , and 37 th series, 28 series, and 29 th and 36 th radiation series. Future researchers can conduct study related to factors that influence chemotherapy and radiation frequencies in cancer patients